Digital disconnect : how capitalism is turning the Internet against democracy - McChesney, Robert Waterman 1952- (New York : The New Press, 2013)
Includes bibliographical references (pages 233-284) and index. What is the elephant in the digital room? -- Does capitalism equal democracy? -- How can the political economy of communication help us understand the Internet? -- The Internet and capitalism I: where dinosaurs roam? -- The internet and capitalism II: empire of the senseless? -- Journalism is dead! Long live journalism? -- Revolution in the digital revolution?